Analysis Of The Role Of Sharia Financing In The Development Of Micro, Small, And Medium Enterprises (MSMEs) (Case Study In The Field Of Sera Suba, Bima City) - M. Nazir; Umar Sagaf; Ibrahim Ibrahim (JURNAL ECONOMINA, 2026)
This study aims to analyze the role of Islamic financing in the development of Micro, Small, and Medium Enterprises (MSMEs) and to identify the types of Islamic financing utilized by MSME actors in Serasuba Square, Bima City. The study employed a qualitative approach with a descriptive research design. Data were collected through observations, in -depth interviews, and documentation involving MSME actors and representatives of Islamic financial institutions providing financing services. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that Islamic financing plays a significant role in supporting MSME development by providing access to capital based on Sharia principles. Islamic financing enables business actors to increase business capacity, expand product inventories, broaden mark et reach, and improve business turnover and income. Furthermore, Islamic financing serves as an alternative funding source that reduces MSMEs’ dependence on high-interest informal loans. The most widely utilized financing scheme is the Murabahah contract, while Mudharabah and Musyarakah contracts are used to a lesser extent. The study concludes that Islamic financing contributes positively to strengthening the economic capacity of MSME actors and supports business sustainability in Serasuba Square, Bima City. The findings also enrich the empirical literature on the role of Islamic financing in local MSME development and provide practical implications for Islamic financial institutions in enhancing financing accessibility for small business actors.